KONSEP, STRATEGI DAN METODE PENDIDIKAN KARAKTER DI MASA PANDEMI COVID 19 - Siti Nur Laelatul Qomariyah; Ari Abi Aufa; Ulfi Nurul Laela (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2021)
The COVID-19 pandemic is still an unresolved problem until now, the coronavirus outbreak that has spread throughout the world including Indonesia has greatly impacted the education process that has been carried out, the education process was supposed to run face-to-face (offline) suddenly turned online. Planting character education for children, strengthening character education in the current context is very relevant to overcome the moral crisis that is happening. The study in this paper is to find strategies and methods of character education during the covid 19 pandemic, with a library research approach the author reviews the results previous research both from research journals, books relevant to character education, the findings of concepts, strategies and methods of character education that can be used are the method of storytelling or storytelling (telling story), discussion methods, simulation methods (role-playing/playing and sociodrama), and live in the method.